COMPARING THE INTERTEMPORAL EFFICIENCY OF ISLAMIC BANKS IN INDONESIA AND MALAYSIA - Lina Nugraha Rani; Salina Kassim (Bank Indonesia, 2020)
This study aims to measure and compare the intertemporal efficiency of Islamic banks in Indonesia and Malaysia using data envelopment analysis (DEA) together with window (intertemporal) analysis for the period 2012–2018 and applying an intermediation approach. Window analysis is used to indicate the stability of efficiency over the study period. The findings show that the intertemporal technical efficiency (TE) of Islamic banks in Indonesia was 77.4% with stability score of 0.034, which was significantly more efficient and more stable than Malaysian banks at 75.1% with stability score of 0.169. Moreover, the the intertemporal pure technical efficiency (PTE) of Islamic banks in Indonesia was 91.7% with stability score 0.020, which was also significantly more efficient and more stable than Malaysian banks at 88.0% PTE and stability score of 0.161. In contrast, the intertemporal scale efficiency (SE) of Islamic banks in Indonesia was 84.5%, slightly lower than that of Malaysian banks at 85.3% but not significantly different. PTE improvement has contributed to TE improvement, while SE has not reached an optimal level. Comparison to previous results also showed that since the global financial crisis the PTEs of Islamic banks in Indonesia and Malaysia have improved while SEs have worsened. Therefore, efforts to improve SE by expanding the size of Islamic banks to reach optimum economies of scale are urgently needed.